Mundane emotions: Losing yourself in boredom, time and technology. (June 2023) - Murphy, Stephen; Hill, Tim; McDonagh, Pierre; Flaherty, Amanda
Marketing and consumer research has drawn attention to the positive and joyful emotional features of consumer tribes. However, research has little to say on boredom, an emotional state already prevalent in consumers' lives, yet exacerbated during the COVID-19 pandemic due to lockdown restrictions that prevented tribal consumption experiences. Informed by Heidegger's understanding of boredom as a fundamental mood tied to temporality, this research uses semi-structured interviews to identify two kinds of boredom – superficial and profound boredom – and their specific temporal dynamics. Superficial boredom is common and refers to a situational restlessness in which people desire distractions. In contrast, profound boredom refers to an existential discomfort in which people struggle with their sense of self, but ultimately can result in the discovery of tribal passions. We explain superficial boredom as a symptom of a dominant temporal regime that comprises connectivity and acceleration. Together these temporal logics fragment and compress time in ways that encourage mundane social media consumption that simply fills time. We also explain how profound boredom stems from an abundance of uninterrupted time spent in relative solitude. In extending Heidegger's theory of boredom to analyse contemporary boredom in an era where digital technology is ubiquitous, our research contributes to consumer research's understanding of mundane emotions and discusses what it means to be bored together.